Factors Associated with Survival Rate in Biliary Atresia Patients Following Kasai Surgery - Agung Aji Prasetyo; Edwin Basyar; Agoes Wibisono; Avriana Pety Wardhani; Banundari Rachmawati; Ignatius Riwanto (RSUP Dr. Kariadi, 2024)
Introduction: Biliary atresia is the most frequent cause of obstructive jaundice leading to liver fibrosis, end-stage liver disease, and death. Kasai surgery offers a bridge to attenuate liver fibrosis progression through reconstruction of the biliary system. The success of the Kasai procedure depends on the presence of jaundice, age at the time of surgery, clay-colored stool, and bilirubin counts. Aim: This study aimed to investigate and predict the death incidence of Biliary atresia patients following Kasai Surgery in our institution. Method: We conducted a case-control study from March 2020 to January 2022 at Kariadi General Hospital, Semarang, Indonesia. We collected data related to gender, age at surgery, albumin level pre and post-surgery, total and direct bilirubin before and after surgery, and the presence of ascites. Bivariate analysis using the Chi-Square test with OR (95% CI) was performed to analyze the risk factors in BA patients following the Kasai procedure. Results: 19 patients with biliary atresia underwent the Kasai procedure with a survival rate of 68.4%. Bilirubin levels ≥10 mg/dL before (p=0.033, OR 11.25) and after (p=0.025, OR 11.00) the Kasai procedure, and the presence of ascites (p=0.005) were significant factors associated with mortality cases. However, a combined multivariate analysis of these factors did not show any significant relationship with outcomes. Conclusion: Bilirubin exceeding 10 mg/dL before and after the Kasai procedure and the presence of Ascites was a marker for poor outcomes for biliary atresia patients following the Kasai procedure